Ambientes virtuais de aprendizagem, mediação e interação : processos da formação online na UFMT - Maieski, Alessandra (2020)
The Virtual Learning Environment (VLE) is extremely relevant as a development space, due to promoting “places/spaces” for other and new appropriation for pedagogical practices. Thus, mainly because of that, there is great importance in research projects, discussions and problematizations about online development processes, as well as in the VLE use. In this dissertation, mediation and interaction are discussed from a historic and social perspective, understanding that these concepts set themselves as elements that promote learning, determining the subject’s relations and roles in online majors. This project was approved by the Ethics Committee in Research (CEP, in Portuguese). The problem of this research project is: how can mediation and interaction processes be identified in online majors of the UFMT? This way, the general goal was to analyze the use of AVA in online majors of the University, in the sense of recognizing, or not, processes and procedures of mediation and interaction. And the specific goals: 1 – Identify the mediation and interaction elements constituted in VLE; 2 – identify the collaborative practices that are developed through it. In terms of methodology, the approach is qualitative, with the participant observation method. The data collected from the Moodle activity reports (Moodle Version 3.1) and through direct observation of nine selected courses take into consideration the use of communication resources available on VLE, in three online majors: Bachelor’s degree in Public Administration (2017); Licentiate degree in Natural Sciences and Mathematics (2017); and Licentiate degree in Pedagogy (2017), offered by the UFMT in the UAB (Open Brazilian University, in English) field. The courses were selected based on a questionnaire applied to students from the three majors. The observation along with the courses was based in four elements for analysis: 1 – Which communication resources were used by the subjects; 2 – How communication happened between them; 3 – Which activities were the foundation for mediation and interaction; 4 – How these activities were organized. Based on the students’ answers in the questionnaires and from the observation done in the courses (as an answer for this research project), we have, then, a stable understanding that mediation and interaction are essentially social, which is the relations made about those participants in the development process, yet specifically not considering what could be an online and in-person crossing, summarizing itself as in-person, i.e., the mediation and interaction happen with the tutor, who is the catalyst for those elements, however it does not consolidate specifically online (VLE), or restricted to it, but especially the understanding that students need in-person moments. The research indicates, hence, that it is necessary to discuss public and institutional policies, professor and tutor’s work, and, in Distance Education’s case, the student’s “role” in the context of digital culture and connected society.